Antimicrobial and antioxidant activities of acetone extract of Ammodaucus leucotrichus Coss. & Dur. seeds (مجلة الواحات للبحوث والدراسات, 2021)
The present study reports the antimicrobial and antioxidant activities of acetone extract of Ammodaucus leucotrichus seeds collected from Béchar provinve (Algeria).The antioxidant activity was evaluated by 2, 2'-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging compared to the synthetic antioxidant (ascorbic acid). The acetone extract showed excellent scavenging activity with an IC50 value of 0.28 mg/mL. The antimicrobial activity was determined using disc diffusion method. The acetone extract at a dose of 2 mg/disc, showed significant antibacterial activity against two bacterial strains (Bacillus subtilis and Escherichia coli) and two yeast species (Candida albicans and Saccharomyces cerevisiae).Key words: Ammodaucus leucotrichus Coss. & Dur., Acetone extract, Antimicrobial activity, Antioxidant activity.